The superliners twilight of an era - Scourby, Alexander; Noxon, Nicolas (WQED/Pittsburg : National Geographic Society, 1980)
A documentary which takes a nostalgic look at the luxury liners such as the Normandie, Titanic, Queen Mary, Queen Elizabeth, and the Queen Elizabeth II, Which plied the North Atlantic in the first half of the twentieth century.
Keywords: Ocean liners